Haitian crisis and the future of collective enforcement of democratic governance. - PIERCE, John C. (1996)
Discusses the international law implications of the collective international management of the Haitian crisis. Points out that the first of such implications is that the international community through the UN, has moved toward the full-scale acknowledgement of an emerging norm of democratic entitlement. Looks at attempts by the OAS and the UN to impose comprehensive economic sanctions as a means of dealing with the Haitian crises and considers whether sanctions are an effective means of influencing crises.